2023
DOI: 10.3390/medicina59030559
|View full text |Cite
|
Sign up to set email alerts
|

Intertrochanteric Femoral Fractures: A Comparison of Clinical and Radiographic Results with the Proximal Femoral Intramedullary Nail (PROFIN), the Anti-Rotation Proximal Femoral Nail (A-PFN), and the InterTAN Nail

Abstract: Background and Objectives: The aim of this study was to evaluate retrospectively the radiological and functional outcomes of closed reduction and internal fixation for intertrochanteric femoral fractures (IFF) using three different proximal femoral nails (PFN). Materials and Methods: In total, 309 individuals (143 males and 166 females) who underwent surgery for IFF using a PFN between January 2018 and January 2021 were included in the study. Our surgical team conducted osteosynthesis using the A-PFN® (TST, Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…There were 310 stable (AO/OTA 31A1) and 1394 unstable (AO/OTA 31A2/A3) fractures in the InterTAN group and 192 stable and 1395 unstable fractures in the comparator group. Fourteen studies enrolled unstable fractures only, 7 studies included both stable and unstable types [ 23 , 24 , 28 30 , 38 , 45 ], and 2 studies did not mention fracture types [ 32 , 34 ]. As to study design, 5 were RCTs [ 23 , 26 , 30 , 41 , 44 ], 2 were prospective observational studies [ 24 , 33 ] and the others were retrospective studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 310 stable (AO/OTA 31A1) and 1394 unstable (AO/OTA 31A2/A3) fractures in the InterTAN group and 192 stable and 1395 unstable fractures in the comparator group. Fourteen studies enrolled unstable fractures only, 7 studies included both stable and unstable types [ 23 , 24 , 28 30 , 38 , 45 ], and 2 studies did not mention fracture types [ 32 , 34 ]. As to study design, 5 were RCTs [ 23 , 26 , 30 , 41 , 44 ], 2 were prospective observational studies [ 24 , 33 ] and the others were retrospective studies.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies (1063 patients) reported mortality after surgery, of which 1 reported in-hospital mortality [ 36 ], 2 reported 1-year mortality [ 34 , 42 ] and 3 reported mortality at last follow-up [ 23 , 39 , 40 ]. Meta-analysis using a fixed-effect model suggested no significant difference in mortality between InterTAN and the comparators (RR = 0.88, 95%CI 0.71 to 1.10, P = 0.266, Additional file 4 : Figure S16).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation